1994
DOI: 10.1021/ic00102a035
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Crystal Structure of Neutral Rhenium(V) Complexes with S-Substituted N2S2 Ligands

Abstract: A series of neutral rhenium(V) oxo complexes was synthesized by the reaction of ReOBr4-with diamino-thiolthioether ligands of the type (RSC(CH~)~CH~NH(O-C&)NHCH~C(CH~)~SH. The complexes were characterized by IR, UVIvisible, and 'H and 13C NMR spectroscopy and by fast-atom-bombardment mass spectroscopy. The single-crystal X-ray structure determination on two of the complexes, where R = CH2CH-CH2 and CH2CH2-CH3, showed them to consist of a square pyramidal ReVON2S2 core. R~O[CH~=CHCHZSC(CH~)~CH~N(~-C6&)NCH2C(CH3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…The ReO1(terminal oxo) has a distance of 1.683(3) Å, while the Re−O2 distance of 2.184(3) Å represents a lengthened single-bond distance, demonstrating the trans influence of the terminal oxo ligand. The Re−S bond lengths of 2.301(1) and 2.377(1) Å are within the range observed for Re(V)−sulfur coordinated complexes.
2 The structure of 3 , showing the atom-labeling scheme and 50% thermal ellipsoids.
…”
Section: Resultssupporting
confidence: 55%
“…The ReO1(terminal oxo) has a distance of 1.683(3) Å, while the Re−O2 distance of 2.184(3) Å represents a lengthened single-bond distance, demonstrating the trans influence of the terminal oxo ligand. The Re−S bond lengths of 2.301(1) and 2.377(1) Å are within the range observed for Re(V)−sulfur coordinated complexes.
2 The structure of 3 , showing the atom-labeling scheme and 50% thermal ellipsoids.
…”
Section: Resultssupporting
confidence: 55%
“…In typical, stable oxorhenium(V) and oxotechnetium(V) complexes, there are often two nitrogen and two sulfur donor atoms; however, most known complexes involve a diamine dithiol (DADT) or similar coordination motif. Though thioether donors are found in stable oxorhenium(V) systems, they have not been extensively investigated. However, there have been some studies of the diamide thioether thiol (DATT) motif, , which has shown interesting properties, such as low binding to blood plasma protein .…”
Section: Resultsmentioning
confidence: 99%
“…In complexes 3a,b and 4a,b the loss of aromatic amine nitrogen hydrogens, which is unusual in amines, may be attributed to the greater acidity imparted to the aniline-like amine hydrogens by conjugation with the aromatic ring. 16 Moreover, only a unique signal for hydrogen (3a,b) and the methyl group (4a,b) of the aromatic nitrogen, respectively, was detected indicating sp 2 hybridization for the aromatic amine nitrogen. Methylene protons of the tetradentate ligand framework were found to be diastereotopic (AB pattern) with coupling constants in the range 17-19 Hz.…”
Section: Preparation Of Rhenium(v) Complexesmentioning
confidence: 99%